Introduction to intelligent systems, control, and machine learning using MATLAB - Schoen, Marco P.; Jain, Ramesh 1949- (New York Cambridge University Press, 2023)
"Dive into intelligent systems, machine learning, and control with this hands-on, project-based textbook, including over 20 hands-on Arduino, Matlab and Simulink assignments. With over 120 end-of-chapter problems, and solutions for instructors, this is the ideal practical introduction for senior and graduate engineering students."
Electronic reproduction
Keywords: MATLAB; Intelligent control systems -- Mathematical models; Machine learning -- Mathematical models; Electronic Resource